Top Four Indian IT Companies: Financial Investigation - Bansal, Rohit; Kar, Sanjay Kumar; Verma, Rakesh Kumar (IIUM Journal of Case Studies in Management, 2021)
This case aims to explain to the students about the various methods for the valuation of a company, get a deep understanding of analyzing the financial statements of a company, and finally base their financial /Investment decisions on such analysis. The case starts with the detailed background of India’s Information Technologies (IT) industry along with that of Top 4 ITs and ITeS companies of India by reviewing their history since incorporation, product and services offerings, revenue, margins, assets, borrowings, and market capitalization. Particularly interested in the current financial position, market position, strategies of the companies, and its peer group.